The Rational and Irrational Factors Underlying Property Buying Behavior - Anastasia, Njo (Journal of Economics and Behavioral Studies, 2015)
Property buying behavior is part of the development of financial behavior. This research will be focused on the buyers perspectives on residential and commercial properties in Bali Island of Indonesia. Rational and irrational factors are the factors underlying the property buying process. The Physical, Location, Environment, Finance factors were part of the rational; while Psychological (over-confidence, conservatism bias, information and familiarity, herd behavior, mental accounting, and loss aversion), Emotion, Intuitional, Socialization, Evaluation were the irrational part. The purpose of this study was, first, to determine the factors that distinguish buyers behavior toward purchasing a property; second, to determine the factors that distinguish buyers behavior between buyers intending to live in compared to those seeking to invest. The study sample consisted of individuals who are prospective buyers and those who have bought property in Bali. Data were analyzed using Discriminant Analysis. The results showed that only financial factor that had significant impact on buyer decisions. Furthermore, this study also showed that there were significant differences in factors between buyers intending to live in compared to those seeking to invest. The factor were psychology, emotion, intuitional, and evaluation.